Nitrogen / metal double-doped silicon carbon negative electrode material and preparation method and application thereof
By using nitrogen/metal double doping technology in the silicon carbon anode material of lithium-ion batteries, the pressure resistance and electrochemical performance of the material are improved, and the problem of low pressure resistance of silicon carbon anode materials in the prior art is solved.
Patent Information
- Application Number
- CN202411548807.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
AI Technical Summary
The current lithium-ion battery silicon carbon anode material has low voltage resistance, which affects the electrical performance of the battery.
Using nitrogen/metal double-doped silicon carbon negative electrode material, the conductivity and strength of the material are improved by doping porous carbon into metals and nitrogen and depositing nanosilicon on its surface.
The voltage resistance and electrochemical properties of silicon-carbon negative electrode materials are significantly improved, the volume expansion of nano-silicon particles is reduced, and the specific capacity of the material is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to new material technology and relates to negative electrode materials for lithium-ion batteries, and specifically to a nitrogen / metal dual-doped silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] As the energy density requirements for lithium-ion batteries continue to increase, the low theoretical capacity of graphite (372 mAh / g) can no longer meet the needs of high-energy lithium-ion batteries. Silicon-carbon anodes are favored for their high theoretical specific capacity (4200 mAh / g) and wide sources of raw materials. In particular, silicon-carbon anode materials prepared by using porous carbon as the skeleton and silicon-source gas deposition of nano-silicon have been widely studied due to their low volume expansion rate.
[0003] Prior art CN117410466A provides a nitrogen-doped silicon-carbon negative electrode material and a preparation method thereof, which uses carbon-containing amine compounds to be pyrolyzed and etched at high temperature to obtain nitrogen-doped porous carbon, then uses silicon source gas to deposit silicon on the nitrogen-doped porous carbon to prepare nitrogen-doped porous carbon / silicon composite particles, and finally uses solid phase or gas phase to carbon-coat the composite particles to obtain nitrogen-doped silicon-carbon negative electrode materials. This technical solution alleviates the structural expansion / contraction of silicon during the discharge / charging process, but does not provide inspiration for solving the low voltage resistance of silicon-carbon negative electrode materials.
[0004] Prior art CN116230911A discloses a high-power silicon-carbon negative electrode composite material and its preparation method. The invention prepares nano-organic metal carbon fiber by electrospinning, and further prepares porous metal carbon fiber by sintering, and then uses gas atomization to deposit nano-silicon in the porous metal carbon fiber, and deposits organic lithium salt on the surface of the core. The preparation method adopted by this technical solution is relatively complicated, and its purpose is to improve the power performance and cycle performance of the silicon-carbon composite material, and does not solve the problem that the pressure resistance of the silicon-carbon negative electrode material needs to be improved.
[0005] Prior art CN117038941A provides a porous silicon-carbon negative electrode material, wherein the porous silicon-carbon negative electrode material is a core-shell structure, wherein the core is a porous hard carbon particle with silicon particles attached to the pores, and the shell is a carbon layer; the metal elements of the metal salt in the hard carbon particle precursor are removed by pickling, thereby forming a porous hard carbon particle with a structure of large internal pores and small external pores, thereby achieving the purpose of increasing the material capacity. This technical solution does not substantially improve the strength of porous carbon, and the preparation is also relatively complicated. It is difficult to obtain a structure with large internal pores and small external pores, and this structure will affect the rate performance of the material.
[0006] Prior art CN115911341A provides a porous silicon-carbon negative electrode material with a core-shell structure, which includes, from the inside to the outside, a porous silicon-sparse carbon core, a transition layer, a dense silicon-carbon layer, and a carbon coating layer, and uses the porous interstitial structure of the porous carbon with silicon particles distributed in the interstitial structure of the carbon skeleton structure to provide excellent flexibility and mechanical strength. The technical solution requires that the structure of the transition layer gradually becomes denser from the porous silicon-sparse carbon core to the dense silicon-carbon layer, which requires a complex preparation process and strict process control, limiting industrial production.
[0007] The silicon-carbon negative electrode material obtained by depositing silane in a porous carbon pore structure is a lithium-ion battery silicon-carbon negative electrode material with great development prospects. However, the pressure resistance of the silicon-carbon negative electrode material affects the electrical properties of the lithium-ion battery prepared therefrom. The existing technology rarely studies the pressure resistance of the silicon-carbon negative electrode material, and the technical solutions disclosed in the few literatures are relatively complicated. Therefore, it is necessary to develop new technical solutions to improve the pressure resistance of the silicon-carbon negative electrode material with a relatively simple preparation process, while improving the electrochemical performance of the silicon-carbon negative electrode material. Summary of the invention
[0008] In the prior art, non-metal-doped porous carbon (such as nitrogen-doped) is often used to prepare silicon-carbon negative electrodes. Although it can improve its rate performance to a certain extent, there is still room for further improvement. In particular, the non-metal-doped carbon matrix cannot improve the pressure resistance of silicon-carbon negative electrode materials. In view of the defects of the prior art, the present invention provides a high-power and high-pressure-resistant silicon-carbon negative electrode material, creatively uses nitrogen / metal dual-doped silicon-carbon negative electrode materials, and doping porous carbon can effectively improve the conductivity and enhance the matrix strength, thereby improving the pressure resistance of the material. Effective silicon deposition (nano-silicon and Si-N-containing particles) reduces the volume expansion of nano-silicon particles and improves the specific capacity of the material; the process for preparing porous silicon-carbon negative electrode materials of the present invention is relatively simple, and doping improves the electrochemical properties of porous carbon.
[0009] The present invention adopts the following technical solution: A nitrogen / metal dual-doped silicon-carbon negative electrode material comprises porous carbon particles with attached nano-silicon, wherein the porous carbon particles with attached nano-silicon are doped with metal and nitrogen. Preferably, the porous carbon particles are metal-doped porous carbon, and the nano-silicon is nitrogen-doped nano-silicon.
[0010] The invention discloses porous carbon particles with nano-silicon attached thereto. The porous carbon particles are metal-doped porous carbon, and the nano-silicon is nitrogen-doped nano-silicon.
[0011] In the present invention, the nitrogen / metal dual-doped silicon-carbon negative electrode material is a core-shell structure, the core is the porous carbon particles attached with nano-silicon, and the shell is a carbon layer. The present invention uses carbon to coat the porous carbon particles attached with nano-silicon, and the nano-silicon clusters are deposited and dispersed in the nano-carbon pores, which can provide a very high reversible capacity and is also a strategy to solve the large volume change of silicon; carbon coating itself is a conventional technology, and gas phase carbon coating, liquid phase or solid phase coating can be used, wherein the gas source used for gas phase coating is one or more of methane, ethane, propane, acetylene, propyne, butyne, propylene, and ethylene.
[0012] In the present invention, the metal is one or more of transition metals, alkaline earth metals, and alkali metals. Preferably, the metal includes one or more of copper, iron, manganese, aluminum, magnesium, potassium, cobalt, silver, and nickel.
[0013] The present invention discloses a method for preparing the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material, comprising the following steps: doping porous carbon with metal and nitrogen, depositing silicon, and obtaining porous carbon particles with attached nano-silicon; then carbon-coating the porous carbon particles with attached nano-silicon to obtain the nitrogen / metal dual-doped silicon-carbon negative electrode material.
[0014] Preferably, the porous carbon loaded with metal compounds is subjected to high temperature treatment to obtain metal-doped porous carbon; then, the metal-doped porous carbon is used as a carrier, and a silicon source gas and a nitrogen source gas are mixed and deposited to obtain porous carbon particles with attached nano-silicon. Furthermore, the porous carbon particles with attached nano-silicon are carbon-coated to obtain the nitrogen / metal dual-doped silicon-carbon negative electrode material.
[0015] In the present invention, the metal compound is one or more of a transition metal compound, an alkaline earth metal compound, and an alkali metal compound. Preferably, the metal compound includes one or more of a copper compound, an iron compound, a manganese compound, an aluminum compound, a magnesium compound, a potassium compound, a cobalt compound, a silver compound, and a nickel compound; preferably, the metal compound includes one or more of a metal chloride, a metal sulfide, and a metal nitrate compound. As an example, the metal compound includes CuCl 2 、FeCl 3 、FeCl 2 、MnCl 3 、AlCl 3 MgCl 2 , KCl, CoCl 3 、AgCl、NiCl 2 One or more of the .
[0016] In the present invention, porous carbon is mixed with a metal compound solution to obtain porous carbon loaded with metal compounds; the specific mixing method is the existing technology, such as using a metal chloride solution to impregnate porous carbon to obtain porous carbon loaded with metal compounds.
[0017] Preferably, the amount of porous carbon is 2% to 70% of the mass of the metal compound solution, preferably 5% to 50%, such as 20%, 30%, 40%, 50% or any percentage within the range; Preferably, the immersion time is 0.25 to 5 h, such as 0.5 h, 1 h, 2 h, 3 h, 4 h or any time within the range.
[0018] Preferably, the porous carbon is mixed with the metal compound solution and then dried to obtain the porous carbon loaded with the metal compound; that is, the porous carbon loaded with the metal compound is dried and then subjected to high temperature treatment to obtain the metal-doped porous carbon. The specific drying method is the existing technology, such as heating drying or spray drying, and the temperature is 150-300°C.
[0019] In the present invention, in the metal compound solution, the solvent includes one or more of water and organic solvents, wherein the organic solvent includes one or more of ethanol, isopropanol, methanol, acetone, dimethylformamide (DMF), G-butyrolactone (GBL), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide (DMA). Preferably, the concentration of the metal compound solution is 0.5-70wt%, preferably 1-50wt%, more preferably 2-30wt%, and more preferably 2-25wt%, for example 3%, 5%, 8%, 10%, 15%, 20%, 25% or any percentage within the range.
[0020] In the present invention, the temperature of high temperature treatment is 400-1200°C, the time is 0.5-5h, preferably the temperature of high temperature treatment is 600-1000°C, the time is 1.5-3.5h; the high temperature treatment is carried out under the protection of inert gas, the inert gas is nitrogen or argon; further, the high temperature treatment is single-stage insulation or segmented insulation, wherein the temperature of the segmented insulation gradually decreases. The modified porous carbon after the above impregnation and high temperature treatment will form a metal-C structure on the pore surface, that is, metal-doped porous carbon will be formed, which can improve the strength of the porous carbon matrix while improving the conductivity. Furthermore, the high temperature stage promotes metal ions to enter the pores and form bonds with the porous carbon pore surface (metal-C bonds).
[0021] In the present invention, the mixed deposition is carried out at a certain temperature and a protective atmosphere, wherein the certain temperature is 300-1000°C, preferably 400-800°C, such as 500°C, 600°C, 700°C or any temperature within the range; the protective atmosphere can be one or more of nitrogen, helium, xenon, radon, neon, argon, or a mixed gas of one or more of the above gases and hydrogen; the mixed deposition time is 1-20h, preferably 2-10h; the flow rate of the silicon source gas is in the range of 10-40 L / min, and the flow rate of the nitrogen source gas is in the range of 0.5-20 L / min, preferably, the flow rate of the silicon source gas is in the range of 15-30 L / min, and the flow rate of the nitrogen source gas is in the range of 1.5-10 L / min. The mixed gas deposition of the silicon source gas and the nitrogen source gas allows the Si-N particles to continuously exist inside and outside the pores of the modified porous carbon.
[0022] In the present invention, carbon coating itself is a conventional technology, and gas phase carbon coating, liquid phase or solid phase coating can be used, wherein the gas source of the gas phase carbon coating includes hydrocarbons, such as the gas source used for gas phase coating is one or more of methane, ethane, propane, acetylene, propyne, butyne, propylene, and ethylene. Preferably, the temperature of the gas phase carbon coating is 300-1000°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or any temperature in the range; preferably, the carbon coating time is 1-10h, such as 2h, 3h, 4h, 5h, 7h, 9h or any time in the range; in the present invention, the gas phase carbon coating insulation process can be a one-stage insulation or a segmented insulation.
[0023] The invention discloses a negative electrode sheet, comprising the porous carbon particles attached with nano-silicon or the nitrogen / metal dual-doped silicon-carbon negative electrode material.
[0024] The invention discloses a lithium ion battery, comprising the negative electrode sheet.
[0025] The invention discloses an electrochemical device, comprising the lithium ion battery.
[0026] The invention discloses the application of the porous carbon particles with nano-silicon attached thereto, the nitrogen / metal dual-doped silicon-carbon negative electrode material or the negative electrode sheet in lithium-ion batteries.
[0027] The present invention provides a nitrogen-doped nano silicon-carbon material with a metal-doped porous carbon matrix. The porous carbon matrix is metal-doped and then a silicon source gas and a nitrogen source gas are added for mixed deposition, thereby improving the conductivity and matrix strength, and improving the deposition uniformity of the material. The prepared silicon-carbon negative electrode material has high conductivity, pressure resistance, and good silicon deposition uniformity. The process is relatively simple and has good application prospects. Specifically, the present invention provides a porous carbon particle with attached nano-silicon, a nitrogen / metal dual-doped silicon-carbon negative electrode material, and an application thereof, which is a silicon-carbon negative electrode material with high power and high pressure resistance. The silicon-carbon negative electrode material prepared by the present invention has good structural stability and excellent performance after being applied to batteries. Moreover, the present invention has low requirements on the manufacturing environment and low cost, and has strongly promoted the development of industrialization of the preparation of silicon-carbon materials by the silane method for lithium-ion batteries with high specific energy density. DETAILED DESCRIPTION
[0028] The present invention discloses a metal / nitrogen doped porous silicon-carbon material and a preparation method and application thereof. The porous silicon-carbon composite negative electrode material is a core-shell structure, wherein the core is porous carbon particles with nano-silicon attached in the pores, and the shell is a carbon layer. The porous carbon particles are metal-doped porous carbon, and the nano-silicon is nitrogen-doped nano-silicon.
[0029] The present invention discloses a method for preparing the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material, comprising the following steps: subjecting porous carbon loaded with metal compounds to high-temperature treatment to obtain metal-doped porous carbon; then using the metal-doped porous carbon as a carrier, using silicon source gas and nitrogen source gas for mixed deposition to obtain porous carbon particles with attached nano-silicon; then carbon-coating the above-mentioned porous carbon particles with attached nano-silicon to obtain the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material.
[0030] In the first stage, porous carbon is impregnated with metal chloride and treated at high temperature to form metal-C on the surface of porous carbon and the surface of pores; in the second stage, a mixed gas of silicon source gas and nitrogen source gas is deposited, so that some Si-N particles are continuously present inside and outside the pores of porous carbon. In the present invention, metal-doped porous carbon is combined with effective silicon deposition (nano-silicon and Si-N-containing particles), which can effectively improve the conductivity and enhance the strength of the matrix, improve the pressure resistance of the material, reduce the volume expansion of nano-silicon particles, and improve the specific capacity of the material.
[0031] As an example of the preparation method, the present invention uses a metal chloride solution to impregnate porous carbon and treat it at high temperature to form a metal-C bond on the surface; the metal chloride solution is a mixture of metal chloride and a solvent, the solvent includes but is not limited to common solvents such as pure water and ethanol, and the metal chloride includes but is not limited to CuCl 2 、FeCl 3 、FeCl 2 、MnCl 3 、AlCl3 MgCl 2 , KCl, CoCl 3 、AgCl、NiCl 2 etc., the proportion of the metal chloride in the solution is 0.5-70wt%; the porous carbon can be prepared according to conventional methods or selected from commercially available products; during the impregnation process, the mass ratio of the porous carbon to the metal chloride solution is 2%-70%, and the impregnation time is 0.25-5h. Preferably, the impregnation process is first stirred and dispersed and then dried; wherein the stirring and dispersion is preferably ultrasonic stirring and dispersion, the time is 0.5-3h, the drying temperature is 60-500℃, preferably 100-300℃, and the drying method can be heating stirring drying or spray drying.
[0032] Furthermore, the high temperature treatment temperature is 400-1300°C, the holding time is 0.5-5h, and the protection process is inert gas protection, and the inert gas is nitrogen or argon; wherein, the holding process can be single-stage holding, such as 800°C, holding for 3h, or segmented holding (such as two or three segments), such as the first segment holding at 900°C, holding for 1h, and the second segment holding at 500°C, holding for 2h. The modified porous carbon after the above impregnation and high temperature treatment will form a metal-C structure on the pore surface, that is, metal-doped porous carbon will be formed, which can improve the strength of the porous carbon matrix while improving the conductivity. The segmented holding is selected, and the high temperature stage promotes the metal ions to enter the pores and form bonds with the porous carbon pore surface (metal-C bonds). The subsequent lower temperature mainly further promotes bonding and promotes the continuous entry of metal ions into the pores. At the same time, the second low temperature can reduce energy consumption.
[0033] Then, the modified porous carbon is placed in the reaction equipment chamber, and a silicon source gas and a nitrogen source gas are used for mixed deposition at a certain temperature and in a protective atmosphere to obtain modified porous carbon particles (porous carbon particles with attached nano-silicon) deposited with nitrogen-doped nano-silicon; the reaction equipment chamber includes conventional chemical vapor deposition equipment such as a fluidized bed and a rotary kiln; the silicon source gas includes one or more of monosilane, disilane, trisilane, and silicon tetrachloride, and the nitrogen source gas includes ammonia; the protective atmosphere can be one or more of nitrogen, helium, xenon, radon, neon, and argon, or a mixed gas thereof with hydrogen. The certain temperature is 300 to 1000°C; the flow rates of the silicon source gas and the nitrogen source gas are in the range of 10 to 40 L / min and 0.5 to 20 L / min, respectively. The mixed gas deposition of the silicon source gas and the nitrogen source gas allows some Si-N particles to continuously exist inside and outside the pores of the modified porous carbon.
[0034] Finally, the modified porous carbon particles with nitrogen-doped nano-silicon deposited and attached in the above pores are carbon-coated to prepare a surface carbon layer to obtain a nitrogen / metal dual-doped silicon-carbon negative electrode material. The carbon coating method is gas phase, liquid phase or solid phase coating, and the gas source used for gas phase coating is one or more of methane, ethane, propane, acetylene, propyne, butyne, propylene, and ethylene; the carbon deposition time is 1 to 8 hours. The temperature of the gas phase carbon deposition is 300 to 1000°C, preferably 400 to 800°C. The gas phase carbon deposition insulation process can be a one-stage insulation or a segmented insulation. Liquid phase and solid phase coating are both commonly used coating methods in this technical field, which will not be repeated here.
[0035] The present invention also provides a negative electrode sheet, comprising the porous carbon particles with attached nano-silicon, or nitrogen / metal dual-doped silicon-carbon negative electrode material. The present invention has no particular restrictions on the preparation method of the negative electrode sheet, and any method known to those skilled in the art can be used.
[0036] For example, the negative electrode active material, conductive material, binder and water are mixed, and the solid content is controlled to be 60-80% to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, dried, and pressed into a sheet to obtain a negative electrode sheet. The negative electrode active material is selected from the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material, or a mixed material of the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material and a graphite negative electrode material; wherein the graphite negative electrode material is one or more of artificial graphite, natural graphite, and modified graphite; when the negative electrode active material is a mixed material of the above-mentioned nitrogen / metal dual-doped silicon-carbon negative electrode material and a graphite negative electrode material, the nitrogen / metal dual-doped silicon-carbon negative electrode material accounts for 30-70% of the mass of the mixed material, preferably 40-60%.
[0037] The bonding material is selected from one or more of acrylonitrile, vinylidene fluoride, vinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, methacryloyl, acrylic acid, lithium acrylate, acrylamide, amide, imide, acrylate, styrene-butadiene rubber, sodium alginate, chitosan, and ethylene glycol; the conductive material is one or more of conductive carbon black, acetylene black, graphite, graphene, carbon micro-nanowires, and carbon micro-nanotubes; the negative electrode current collector may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, foam nickel, foam copper, or a composite current collector.
[0038] The negative electrode active material, conductive material and binding material are mixed in mass percentages of 80-99%, 0.5-5% and 1-10%, respectively. The mass percentage of the negative electrode active material is preferably 85-98%, 90-97%, 91-95%, 92-94% and 92-93%.
[0039] The present invention also provides a lithium ion battery, comprising the above-mentioned negative electrode sheet. The specific preparation method and composition of the lithium ion battery are not particularly limited, and methods known to those skilled in the art can be used, which may include but are not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery, etc.
[0040] As an example, a negative electrode sheet, a separator, and a positive electrode sheet are wound to obtain a battery cell, and the battery cell is placed in a battery case, dried, injected with electrolyte, packaged, formed, and divided into different capacities to obtain a lithium-ion battery.
[0041] Various exemplary embodiments of the present invention are now described in detail, and the detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the field of the present invention. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. The raw materials used in the present invention are existing products that meet the conventional requirements of silicon-carbon negative electrode materials for lithium-ion batteries. Specific preparation operations (such as dispersion, mixing, drying, heat treatment and other specific operations) and performance tests are all conventional techniques.
[0042] Porous carbon is a common porous carbon material on the market. The particle sizes of D00, D50 and D100 are 2.1-2.5, 8.5-9.3 and 18-23 respectively, and the specific surface area is 2050-2200 m 2 / g, pore volume 1.0-1.2 cm 3 / g, average pore size 2.0-2.2nm. Those skilled in the art can also prepare it according to conventional methods. Unless otherwise specified, the silane used in the experiment is monosilane.
[0043] The carbon content is determined using a carbon-sulfur analyzer using the high-frequency combustion infrared absorption method. Embodiment 1
[0044] Impregnation of porous carbon doped with metal: 25 kg of copper chloride solution was prepared by dissolving copper chloride in ethanol, the concentration of the copper chloride solution was 8 wt %, and 5 kg of porous carbon was added after complete dissolution, and the mass ratio of porous carbon to copper chloride solution was 20 wt % in the formed mixture of porous carbon and copper chloride solution. The mixture of porous carbon and copper chloride solution was ultrasonically stirred for 1 hour and then spray-dried to obtain modified porous carbon at a spray drying temperature of 200 ° C; then high-temperature treatment was performed at a heat treatment temperature of 700 ° C for 3 hours, and the protective gas was nitrogen to obtain a modified porous carbon material containing metal-C; Silicon deposition: The modified porous carbon after high temperature treatment is placed in the fluidized bed chamber, and silane and ammonia are introduced at the same time, with gas flow rates of 22.5 L / min and 2.5 L / min respectively. The protective gas is nitrogen, with a gas flow rate of 25 L / min. The deposition time is 6.5 h and the deposition temperature is 540 ° C. After deposition, porous silicon-carbon negative electrode material (porous carbon particles with attached nano-silicon) is obtained. Carbon coating: The porous carbon particles with attached nano-silicon were subjected to conventional gas-phase carbon coating. The carbon source gas used was acetylene, the protective gas was nitrogen, the acetylene and nitrogen flow rates were 20 L / min and 18 L / min, respectively, and the coating process was kept at 650°C for 5 hours. A nitrogen / metal dual-doped silicon-carbon negative electrode material was obtained, and its carbon content was 45.9wt%. Embodiment 2
[0045] Refer to Example 1, except that the mass ratio of porous carbon to cupric chloride solution is 30wt%; the rest is the same, and finally the carbon coating obtains nitrogen / metal dual-doped silicon-carbon negative electrode material, whose carbon content is 47.2wt%. Embodiment 3
[0046] Refer to Example 1, except that the mass ratio of porous carbon to cupric chloride solution is 40wt%; the rest is the same, and finally the carbon coating is performed to obtain nitrogen / metal dual-doped silicon-carbon negative electrode material, whose carbon content is 47.9wt%. Embodiment 4
[0047] Refer to Example 1, except that: the mixture of porous carbon and cupric chloride solution is ultrasonically stirred for 1 hour and then only mechanically stirred, the stirring temperature is 70°C, the rotation speed is 200r / min, stirred until it is in a gel state, and then dried, ground (crushed), and sieved (300 mesh) to obtain modified porous carbon; the rest is the same, and finally carbon coating is obtained to obtain nitrogen / metal dual-doped silicon-carbon negative electrode material, whose carbon content is 45.7wt%. Embodiment 5
[0048] Referring to Example 1, the difference is that the high temperature treatment temperature is 900°C, the heat treatment time is 3 hours, and the rest is the same. Finally, the carbon coating is performed to obtain a nitrogen / metal dual-doped silicon-carbon negative electrode material, and the carbon content is 45.8wt%. Embodiment 6
[0049] Impregnation of porous carbon doped with metal: aluminum chloride was dissolved in ethanol to prepare an aluminum chloride solution, the concentration of which was 10 wt %. After the aluminum chloride solution was completely dissolved, 5 kg of porous carbon was added, and the mass ratio of porous carbon to aluminum chloride solution was 30 wt %. The mixture of porous carbon and aluminum chloride solution was ultrasonically stirred for 1 hour and then spray dried at a spray drying temperature of 200 ° C. Perform high temperature heat treatment according to Example 5 to obtain a modified porous carbon material after high temperature treatment; Silicon deposition is performed according to Example 1, and a porous silicon-carbon negative electrode material is obtained after the deposition is completed; Carbon coating was performed according to Example 1 to obtain a nitrogen / metal dual-doped silicon-carbon negative electrode material with a carbon content of 46.8 wt %. Embodiment 7
[0050] Refer to Example 6, except that the concentration of the aluminum chloride solution is 15wt%; the rest is the same, the deposition is completed to obtain a porous silicon-carbon negative electrode material, and finally carbon coating is performed to obtain a nitrogen / metal dual-doped silicon-carbon negative electrode material with a carbon content of 45.0wt%. Embodiment 8
[0051] Impregnation of porous carbon doped with metal: using ethanol to dissolve manganese chloride to prepare a manganese chloride solution, the concentration of the manganese chloride solution is 10wt%, after complete dissolution, 5kg of porous carbon is added, the mass ratio of porous carbon to manganese chloride solution is 30wt%, the mixture of porous carbon and manganese chloride solution is ultrasonically stirred for 1 hour and then spray dried, the spray drying temperature is 200°C; The high temperature treatment is performed according to Example 5 to obtain a modified porous carbon after high temperature treatment; Silicon deposition is performed according to Example 1, and a porous silicon-carbon negative electrode material is obtained after the deposition is completed; Carbon coating was performed according to Example 1 to obtain a nitrogen / metal dual-doped silicon-carbon negative electrode material with a carbon content of 46.7 wt %. Embodiment 9
[0052] Referring to Example 1, the difference is that the coating method used for carbon coating is asphalt coating, and a nitrogen / metal dual-doped silicon-carbon negative electrode material is obtained.
[0053] Asphalt coating is a conventional technology, which is briefly described as follows: porous carbon particles attached with nano-silicon are evenly mixed with high-temperature petroleum asphalt powder with a softening point of 230°C in a mass ratio of 10:3, placed in a hot press and vacuum hot pressed at 260°C for 0.5h to obtain an asphalt-coated material, which is then heated to 700°C in a nitrogen atmosphere for carbonization treatment for 2h, and after crushing and screening, the silicon-carbon negative electrode material is obtained.
[0054] Comparative Example 1 Nitrogen Doping Only Referring to Example 1, the difference is that the copper chloride mixed impregnation process is omitted, and only a high temperature treatment of 700°C / 3h is performed. That is, the porous carbon of Comparative Example 1 is not impregnated and dried, but only subjected to high temperature treatment, and is directly placed in a fluidized bed for silicon source and nitrogen source gas deposition, and the silicon deposition and carbon coating processes are the same as those of Example 1.
[0055] Comparative Example 2: Metal doping only Refer to Example 1, the difference is that only silane gas and nitrogen are passed during the silicon deposition process, and other conditions remain unchanged. Finally, carbon coating is performed to obtain a metal-doped silicon-carbon negative electrode material.
[0056] Comparative Example 3: No doping Referring to Comparative Example 1, the difference is that only silane gas and nitrogen gas are passed during the silicon deposition process (ie, the deposition process is the same as that of Comparative Example 2), and other conditions remain unchanged, and finally a silicon-carbon negative electrode material is obtained.
[0057] The electrochemical performance test is a conventional method, which is briefly described as follows.
[0058] The prepared silicon-carbon composite negative electrode material, acetylene black and sodium carboxymethyl cellulose (CMC) were mixed and beaten in a mass ratio of 8:1:1 to form a slurry, coated on copper foil, and baked in a vacuum oven at 85°C for 10 hours. The dried pole piece was then cut into a disc with a diameter of 14 mm and assembled with a lithium sheet into a button battery, wherein the aqueous electrolyte of the assembled lithium-ion battery was 1 mol / L lithium hexafluorophosphate (LiPF6), and the solvent of the electrolyte was ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, DMC, and DEC was 1:1:1. The diaphragm was a polyethylene diaphragm. Finally, the electrochemical performance was tested in the blue battery test system, voltage window: 0.01V-2V; discharge rate: 0.1C.
[0059] The full-charge expansion rate test is the expansion of the electrode sheet, and the calculation method is the ratio of the difference in electrode sheet thickness before and after full charge to the electrode sheet thickness before full charge. The electrode sheet thickness before full charge refers to the electrode sheet thickness when not charged.
[0060] The method of the buckle expansion test is as follows: first, measure the thickness of the negative electrode sheet, recorded as D1, and measure the thickness of the copper foil current collector substrate, recorded as D2, and discharge at a rate of 0.1C. After the discharge, disassemble the battery in the glove box, take out the silicon-carbon negative electrode sheet, and measure the thickness of the negative electrode sheet at this time, recorded as D3. Calculate the first expansion rate, formula: first expansion rate = (D3-D1) / (D1-D2)×100%.
[0061] The above-mentioned discharge is a lithium insertion process, corresponding to the charging in the full battery; the charging is a lithium removal process, corresponding to the discharge of the full battery.
[0062] The powder resistivity pressure is 200kg.
[0063] The voltage resistance test is to evaluate the changes in the electrochemical properties of the sample before and after pressing (the silicon-carbon negative electrode material slurry prepared by the same method is divided into two groups, one group is not pressed as before pressing, and the other group is pressed as after pressing). The voltage resistance test condition is to measure the buckling performance after the coated electrode is rolled by a roller press at 80Mpa.
[0064] Table 1 Performance of silicon-carbon anode materials
[0065] Table 1 shows the performance of the above-mentioned silicon-carbon negative electrode material. According to Table 1, matrix metal / nitrogen doping can effectively improve the strength and conductivity of the porous carbon matrix, improve the first effect after compression of the porous silicon-carbon negative electrode, and also improve the volume expansion of the silicon material; the porous carbon matrix metal doping and deposited silicon nitrogen doping of the present invention can synergistically promote and improve the deposition uniformity and conductivity of the material.
[0066] The present invention performs metal doping on the porous carbon matrix by impregnation and high temperature treatment; silicon deposition adopts mixed deposition of nitrogen-containing source gas and silicon source gas to achieve nitrogen-doped silicon deposition, promote uniform deposition of silicon, and reduce the volume expansion of nano-silicon; matrix metal doping and deposited silicon nitrogen doping can synergistically promote uniform deposition of silicon, effectively improve conductivity, and also improve the withstand voltage of silicon-carbon negative electrode. It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not used to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range and any other stated value or each smaller range between the intermediate values within the range are also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range. It is obvious to those skilled in the art that various improvements and changes can be made to the specific embodiments of the present invention specification without departing from the scope or spirit of the present invention. Other embodiments obtained from the description of the present invention are obvious to the technician. The present invention specification and examples are exemplary only.
Claims
1. A nitrogen / metal dual-doped silicon-carbon negative electrode material, comprising porous carbon particles attached with nano-silicon, characterized in that: The porous carbon particles with nano-silicon attached thereto are doped with metal and nitrogen.
2. The nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1, characterized in that: The nitrogen / metal dual-doped silicon-carbon negative electrode material is a core-shell structure, wherein the core is the porous carbon particles with attached nano-silicon, and the shell is a carbon layer.
3. The nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1, characterized in that: The porous carbon particles are metal-doped porous carbon, and the nano-silicon is nitrogen-doped nano-silicon.
4. A porous carbon particle with attached nano-silicon, characterized in that: The porous carbon particles are metal-doped porous carbon, and the nano-silicon is nitrogen-doped nano-silicon.
5. The nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1 or the porous carbon particles with nano-silicon attached according to claim 4, characterized in that: The metal is one or more of transition metals, alkaline earth metals and alkali metals.
6. The method for preparing the nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1 or the porous carbon particles attached with nano-silicon according to claim 4, characterized in that: The method comprises the following steps: doping porous carbon with metal and nitrogen, depositing silicon, and obtaining porous carbon particles with attached nano-silicon; and then carbon coating the porous carbon particles with attached nano-silicon to obtain nitrogen / metal dual-doped silicon-carbon negative electrode material.
7. The method for preparing the nitrogen / metal dual-doped silicon-carbon negative electrode material or the porous carbon particles with attached nano-silicon according to claim 6, characterized in that: The porous carbon loaded with metal compounds is treated at high temperature to obtain metal-doped porous carbon; then, the metal-doped porous carbon is used as a carrier and mixedly deposited using silicon source gas and nitrogen source gas to obtain porous carbon particles with attached nano-silicon; then, the porous carbon particles with attached nano-silicon are carbon-coated to obtain the nitrogen / metal dual-doped silicon-carbon negative electrode material.
8. The preparation method according to claim 7, characterized in that: The metal compound includes one or more of metal chloride, metal sulfide and metal nitrate; porous carbon is mixed with a metal compound solution to obtain porous carbon loaded with metal compounds; the temperature of high temperature treatment is 400-1300°C and the time is 0.5-5h; mixed deposition is carried out at a certain temperature and a protective atmosphere; the certain temperature is 300-1000°C; the protective atmosphere is one or more of nitrogen, helium, xenon, radon, neon and argon.
9. A negative electrode sheet, comprising the nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1 or the porous carbon particles with attached nano-silicon according to claim 4; or, a lithium-ion battery, comprising the negative electrode sheet.
10. Use of the nitrogen / metal dual-doped silicon-carbon negative electrode material according to claim 1, the porous carbon particles with attached nano-silicon according to claim 4, or the negative electrode sheet according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Porous silicon carbon negative electrode material, preparation method and application
CN115911341A
High-power silicon-carbon negative electrode composite material and preparation method thereof
CN116230911A
Porous silicon carbon negative electrode material and preparation method and application thereof
CN117038941A
Nitrogen-doped silicon-carbon negative electrode material and preparation method thereof
CN117410466A
Cited By
Power type silicon-carbon composite material and preparation method thereof
CN120854525A